Peran Guru PAI Terhadap Prilaku Sopan Santun Siswa di SMA Muhammadiyah 3 Jakarta - Humairo Azizah; Totong Heri (Departement of Mathematics Education, 2024)
This research was triggered by the uncommendable behavior of adolescents in the school environment. There are various factors, causes, and positive and negative impacts of these behaviors. One of the positive impacts of adolescent poor behavior carried out by students is the formation of many new friends and experiences. But one of the negative effects is being disrespectful to older people. This is greatly influenced by the child's social environment. Adolescents are prone to emotional instability, confusion in decision-making, and prone to anger when facing problems. The task of Islamic Religious Education (PAI) teachers is to overcome student behavior through a disciplinary approach. The purpose of this study is to improve the ability of PAI teachers to overcome juvenile delinquency in schools with a disciplined approach, to form disciplined students.